PS 07-16 CROSSTALK BETWEEN ALDOSTERONE-STIMULATED MINERALOCORTICOID RECEPTOR AND ANGIOTENSIN RECEPTOR PATHWAYS PLAYS A ROLE IN ALDOSTERONE-INDUCED VASCULAR INJURY. (September 2016) - Paradis, Pierre; Briet, Marie; Barhoumi, Tlili; Mian, Muhammad Oneeb Rehman; Coelho, Suellen C.; Rautureau, Yohann; Coffman, Thomas M.; Schiffrin, Ernesto L.
Abstract : Objective: Aldosterone is known to induce hypertension and vascular injury. A large body of evidence suggests a crosstalk between aldosterone and angiotensin II pathways. We demonstrated in vitro that vascular smooth muscle cell activation of signaling pathways such as ERK1/2 requires functional angiotensin type 1a receptor (AGTR1A). We hypothesized that aldosterone-induced vascular damage require AGTR1A. Design and Method: Wild-type and Agtr1a knockout ( Agtr1a −/− ) mice were infused with aldosterone (600 μg/Kg/d) for 14 days while receiving 1% saline in drinking water. Systolic blood pressure (SBP) was measured by telemetry. Endothelial function and vascular remodeling using pressurized myography, reactive oxygen species (ROS) production by dihydroethidium staining, collagen content by Sirius red staining, fibronectin, and monocyte chemotactic protein-1 (MCP-1) expression by immunofluorescence and mRNA expression of mineralocorticoid receptor (MR) target genes regulating vascular tone by reverse transcription-quantitative PCR were assessed in mesenteric arteries. Natriuretic responses to a saline challenge was assessed using metabolic cage. Results: Aldosterone increased SBP by ∼30 mmHg in wild-type mice, and ∼50 mmHg in Agtr1a −/− mice. Aldosterone induced vascular remodeling and impaired endothelium-dependent relaxation in wild-type mice, and enhanced fibronectin and collagen deposition, and vascular inflammation. None of these vascular effects were observed in Agtr1a −/− mice. Agtr1a −/− mice infused with aldosterone did not increase sodium excretion in response to a sodium chloride challenge, suggesting sodium retention that could contribute to the exaggerated blood pressure rise induced by aldosterone. Agtr1a −/− mice had decreased mesenteric artery expression of the calcium-activated potassium channel Kcnmb1, which may enhance myogenic tone and together with sodium retention exacerbate BP responses to aldosterone/salt in Agtr1a −/− mice. Conclusions: We conclude that although aldosterone activation of MR raises BP more in Agtr1a −/− mice, AGTR1a is required for MR stimulation to induce endothelial dysfunction and vascular remodeling and inflammation.